Sifat Mekanik Bata Beton Dengan Penambahan Styrofoam - Steffani, Anggia; Djauhari, Zulfikar; Ismeddyanto, Ismeddiyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Technological advancements have directed infrastructure development in light and strong materials. Styrofoam can be used as a substitute for fine aggregates in concrete bricks, and can reduce the weight of concrete bricks with strengths that still meet the current standards The purpose of this study was to examine the effect of adding styrofoam to the mechanical properties of concrete bricks. In this study, the composition of the mixture used is 1 cement : 3 sand with variations of styrofoam as a substitute for sand at 0%, 5%, 10% and 15%. The size of the test object carried out in this study was 39x9x10 cm, the number of test items were 12 pieces and the treatment of the specimen was done by covering the test object with wet burlap for 28 days. The results showed that, the average compressive strength of the specimens contained 0% of styrofoam was 64.83 kg/cm2, 5% of styrofoam was 54.24 kg/cm2, 10% of styrofoam was 49.45 kg/cm2, and 15% of styrofoam was 45.75 kg/cm2. Furthermore, the compressive strength of specimens contained 0%, 5%, 10% and 15% of styrofoam was met the grade III of the concrete bricks criteria suggested by SNI 03-0349-1989. Keywords: Styrofoam, Concrete Brick, Compressive Strength.